Pengaruh Pelatihan Terhadap Kinerja Karyawan Dipt Trafoindo Prima Perkasa - adminojs adminojs; Milawati; Yohannes Don Bosko; Elisabeth Fransiska Bowleyn (Journal Management SMC, 2022)
ABSTRACT The purpose of this study was to analyze the effect of training on the performance of Dipt Trafoindo Prima Perkasa employees. This study uses a qualitative descriptive research method. The research was conducted at PT Trafoindo Prima Perkasa Central Jakarta, based on the following considerations: The researcher had made observations and was interested in researching at PT Trafoindo Prima Perkasa Central Jakarta and the researcher considered time, cost and manpower because the location was affordable for the researcher. The subjects of this study were employees of PT Trafoindo Prima Perkasa, Central Jakarta, who were the main informants. Data collection techniques used are: Observation, Interview and Documentation. Data analysis in this study used qualitative methods which were carried out before entering the field, while in the field and after finishing in the field. The results of the study show that: first, the training conducted by PT Trafoindo Prima Perkasa has been going on for approximately 10-20 years. PT Trafoindo Prima Perkasa's training methods are On The Job Training, in door training, out door training, in class, knowledge sharing and factory visits, Training materials are tailored to the needs of the company and employees, while training instructors come from internal and external sources. Second, the employee's view of training is being able to get to know the structure and regulations within the company, increasing skills and knowledge at work, as well as increasing experience and in accordance with work. Keywords: Training, employee performance